E-COMMERCE AND “GREEN” INNOVATIONS - Pivkach , Iryna (Collection of scientific papers «ΛΌГOΣ», 2025)
In modern conditions innovative economic development is the only possible path for progressive technological progress and growth of well-being in developed countries. At the same time, radical innovations and breakthrough scientific achievements are capable of having a significant impact on the global economy. The development of science, research and development remains the key to the implementation of all types of technological innovations.